2016
DOI: 10.1097/adm.0000000000000250
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association Between Internalizing Symptoms and Craving in Methamphetamine Users

Abstract: Objectives Methamphetamine (MA) users often have substantial psychiatric comorbidities, with nearly a third reporting lifetime mood disorders and over a quarter reporting lifetime anxiety disorders. Female MA users are more likely to endorse depression and anxiety symptoms compared to men. Craving has been related to mood/anxiety symptoms in MA users. To extend the literature on gender differences in MA use disorder, the present study examines the role of gender as a moderator of the relationship between mood/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
10
1
Order By: Relevance
“…Beck Depression Inventory (BDI) is used to assess specific depression symptoms ( 24 26 ). Additionally, there are several other assessments used in MAP research, including the Beck Anxiety Inventory (BAI) ( 27 , 28 ), Hamilton Depression Rating Scale (HDRS) ( 29 , 30 ), and other scales ( 31 33 ). There is inconsistency in MAP definition when several assessments are compared ( 34 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beck Depression Inventory (BDI) is used to assess specific depression symptoms ( 24 26 ). Additionally, there are several other assessments used in MAP research, including the Beck Anxiety Inventory (BAI) ( 27 , 28 ), Hamilton Depression Rating Scale (HDRS) ( 29 , 30 ), and other scales ( 31 33 ). There is inconsistency in MAP definition when several assessments are compared ( 34 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among 113 female methamphetamine users participating in a compulsory detoxification program (average detoxification duration of 8.7 ± 4.8 months), craving level positively correlated with negative mood disturbances including fatigue, bewilderment, anxiety, depression, and hostility after controlling for each user's weekly dose of methamphetamine (34). Alternatively, among a sample of 203 non-treatment seeking methamphetamine users, the opposite pattern was observed, wherein depression and anxiety symptoms positively correlated with methamphetamine craving among men, but not women (31). This difference in findings may be related to use status at the time data were collected, given that two studies reported on abstinent users (34,73) and one examined current users (31).…”
Section: Sex-specific Findingsmentioning
confidence: 92%
“…Alternatively, among a sample of 203 non-treatment seeking methamphetamine users, the opposite pattern was observed, wherein depression and anxiety symptoms positively correlated with methamphetamine craving among men, but not women (31). This difference in findings may be related to use status at the time data were collected, given that two studies reported on abstinent users (34,73) and one examined current users (31). Gender differences have also been observed among self-reported reasons for use.…”
Section: Sex-specific Findingsmentioning
confidence: 99%
“…It is more rapid and provides voxel-wise whole brain results compared to manually segmented brain regions in traditional morphometric approaches ( Ashburner and Friston, 2000 ). Therefore, it has been extensively used in psychiatric disorder studies including substance addiction ( Morales et al, 2012 ; Durazzo et al, 2015 ; Hartwell et al, 2016 ). As another important structural analysis method, surf-based cortical thickness measurement allows the “regional distribution and quantification of gray matter cortical loss to be specifically assessed in contrast to gyral or lobar volumetric studies which combine gray and white matter within regional volumes” ( Rohrer et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%